2013
DOI: 10.1136/archdischild-2012-303303
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of different oral formulations in infants and preschool children

Abstract: ObjectiveLiquid medicines are easy to swallow. However, they may have disadvantages, such as a bad taste or refrigerated storage conditions. These disadvantages may be avoided by the use of oral solid medicines, such as powders or tablets. The aim of this study was to investigate the acceptability of and preference among four oral formulations in domiciliary infants and preschool children in The Netherlands.MethodsParents administered four oral placebo dosage forms that were aimed at a neutral taste, at home, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(90 citation statements)
references
References 18 publications
1
77
0
7
Order By: Relevance
“…Recent studies assessing the acceptability and swallowability of placebo mini-tablets have been a notable emergence in the field, particularly as a dosage form for neonates and infants (Klingmann et al, 2013, Klingmann et al, 2015, Thomson et al, 2009, van Riet-Nales et al, 2013, Kluk et al, 2015. An important objective of 235 the CALF study was to determine acceptability and perceptions of these dosage forms in older children, since very little is reported in the literature.…”
Section: Novel Dosage Formsmentioning
confidence: 99%
“…Recent studies assessing the acceptability and swallowability of placebo mini-tablets have been a notable emergence in the field, particularly as a dosage form for neonates and infants (Klingmann et al, 2013, Klingmann et al, 2015, Thomson et al, 2009, van Riet-Nales et al, 2013, Kluk et al, 2015. An important objective of 235 the CALF study was to determine acceptability and perceptions of these dosage forms in older children, since very little is reported in the literature.…”
Section: Novel Dosage Formsmentioning
confidence: 99%
“…mini-tablets, has already been discussed elsewhere. In summary, we have found that 4-mm uncoated mini-tablets can be used successfully in children from 1 year of age (46). In addition, Klingmann et al showed that smaller 2-mm minitablets can be used in infants from 6 months of age, whereas 2 mm rapidly dissolving mini-tablets can be used as early as in the pre-term age (47,48).…”
Section: Mini-tabletsmentioning
confidence: 97%
“…This claim is supporting to our result. 9 As shown in Table II, out of total drugs prescribed most common drugs were antihistaminic followed by respiratory drugs, vitamins, analgesics and antibiotics. Antihistaminics were also most commonly prescribed medicines in study done by Cuvillo AD et al 10 Study conducted by Tzimis L et al showed, antipyretics, antibiotic, cough & cold preparations and vitamins were the commonest category of drugs prescribed.…”
Section: Discussionmentioning
confidence: 99%